2017
DOI: 10.1002/2017gl076113
|View full text |Cite
|
Sign up to set email alerts
|

Drop Height and Volume Control the Mobility of Long‐Runout Landslides on the Earth and Mars

Abstract: Long-runout landslides are landslides with volumes of 10 5 m 3 or more, which move much farther from their source than expected. The observation that Martian landslides are generally less mobile than terrestrial landslides offers important evidence regarding the mechanism responsible for the high mobility of long-runout landslides. Here we simulate landslides as granular flow using a soft-particle discrete element model. We show that while surface gravity plays a negligible role, observed differences in fall h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 37 publications
3
26
0
Order By: Relevance
“…Runs with no reported particle size assume D = 1 m. Each point represents the result of a landslide simulation. The results for Earth and Mars surface gravity were reported previously byJohnson et al (2016) andJohnson and Campbell (2017). Note g Earth = 9.8 m/s 2 , g Mars = 3.7 m/s 2 , and g Ceres = 0.27 m/s 2 .…”
supporting
confidence: 79%
“…Runs with no reported particle size assume D = 1 m. Each point represents the result of a landslide simulation. The results for Earth and Mars surface gravity were reported previously byJohnson et al (2016) andJohnson and Campbell (2017). Note g Earth = 9.8 m/s 2 , g Mars = 3.7 m/s 2 , and g Ceres = 0.27 m/s 2 .…”
supporting
confidence: 79%
“…20 • (Farin et al, 2014;Borykov et al, 2019), whereas it has no influence for more gentle slopes. This dependency of landslide propagation on slope, and indirectly on volume (and friction), initially identified in lab- oratory experiments (Farin et al, 2014) could be adequately documented by natural examples thanks to some very large Martian landslides (Johnson and Campbell, 2017;Borykov et al, 2019), much larger than any terrestrial landslide, which help populate the landslide dataset for voluminous landslides that propagate on nearly flat surfaces. Similar to landslides, DSGSD occurs on mountain slopes that are much smaller on Earth than on Mars, and at the first order, their origin may be similar.…”
Section: Scaling Of Processes Involved In Deep-seated Gravitational Smentioning
confidence: 73%
“…Although similar at first order, landslide propagation is not controlled by the same parameters because the landslide slope is different. It was shown that landslide volume is one of the factors that control landslide propagation (McEwen, 1989;Lucas et al, 2014;Johnson and Campbell, 2017) when the slope angle of the propagation plane is steeper than ca. 20 • (Farin et al, 2014;Borykov et al, 2019), whereas it has no influence for more gentle slopes.…”
Section: Scaling Of Processes Involved In Deep-seated Gravitational Smentioning
confidence: 99%
“…Accordingly, our research team proposed that thermal pressurization induced by frictional heating may be a key factor in the frictional weakening of the avalanche basal facies samples, which provides insight into rock avalanche hypermobility mechanisms. This discovery brings to mind another rock avalanche feature revealed by field data statistics: the reduction of Fahrböschung with increasing rock avalanche volume, that is, rock avalanche volume effect (Johnson & Campbell, ; Legros, ; Lucas et al, ; Pudasaini & Miller, ).…”
Section: Introductionmentioning
confidence: 98%